CHARACTERISTICS AND RISK FACTORS FOR MORTALITY IN PATIENTS HOSPITALIZED BY COVID-19 IN A PUBLIC HOSPITAL IN TACNA - Hueda Zavaleta, Miguel (2021)
ABSTRACT Objective: The objective of the study was to describe the clinical, laboratory and treatment characteristics of patients hospitalized for COVID-19 and to determine the risk factors for hospital mortality. Methods: Retrospective cohort study of adult patients hospitalized for COVID-19. Clinical, laboratory and treatment data were extracted from the medical records of patients admitted to Level III Daniel Alcides Carrión-Tacna Hospital. Survival analysis used the Cox proportional hazards model and crude and adjusted hazard ratios (HR) were calculated with their respective 95% confidence intervals (95% CI). Results: 351 patients were evaluated, 74.1% were men, the most common comorbidities were obesity (31.6%), hypertension (27.1%) and diabetes mellitus (24.5%). The median time of hospitalization was 8 days (IQR: 4-15). 32.9% died during follow-up. The multivariate analysis showed an increased risk of dying associated with age> = 65 years HR = 3.55 (95% CI: 1.70-7.40), increase in lactate dehydrogenase> 720 U / L HR = 2.08 (95% CI: 1.34-3.22), and oxygen saturation less than 90%, mainly when it was less than 80% RH = 4.07 (95% CI: 2.10-7.88). In addition, within the treatment, colchicine showed a protective effect HR = 0.46 (95% CI: 0.23-0.91). Conclusions: Risk factors for mortality from COVID-19 included being older than 65 years, having oxygen saturation less than 90%, and elevated lactate dehydrogenase> 720 U / L; colchicine treatment could improve the prognosis of patients.